PENGGUNAAN APLIKASI ATLAS TERHADAP KINERJA AUDITOR - Pradana, Rifandi Argi; Ardiami, Kinanthi Putri (Universitas Muhammadiyah Palembang, 2023)
The purpose of this study was to determine whether using ATLAS has an effect on auditor performance as measured by work quality, work quantity, and timeliness with several indicators. The methodology used is qualitative based on observations and interviews with senior auditors at KAP KKSP. The results of this study are ATLAS affects the quality of work on indicators of misstatement detection, compatibility with applicable general standards, and compliance with SOPs. On work quantity, ATLAS affects the indicator of the amount of work that can be completed with targets within a certain time but has no effect on the ability to utilize facilities and infrastructure where ATLAS is positioned as a tool in accommodating audit procedures. Finally, ATLAS affects the timeliness of auditors in completing their work. The limitation of this research is that it is only based on one KAP and is only limited to the offline version of ATLAS.